Investigation of University Students' Realization of the Benefits of Leisure Activities - ÜSTÜN, Ümit Doğan; AKTAŞ ÜSTÜN, Neslişah (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
This study aimed to examine the awareness of Hatay Mustafa Kemal University students about the benefits of recreational activities. Eight hundred twenty students studying in different faculties at Tayfur Ata Sökmen Campus voluntarily participated in the study. The participants were chosen according to the random sampling method. To collect data Recreation Awareness Scale which was developed by Ekinci and Özdilek in 2019 was used. The scale is a self-report scale and has three sub-scales and 41 items. The data were analyzed with SPSS for Windows 23 package program using independent samples t-test and One-way ANOVA in addition to descriptive statistics such as frequency and percentage. According to the analysis results, the participants had the highest realization in the self-development sub-dimension and the lowest realization in the social success sub-dimension. Besides, although there were no significant differences in the variable awareness subscale scores according to gender and class, there were significant differences according to interest in sport and social student club membership status. As a result, this paper showed that students interested in sports in various ways and who are the members of a social student club are more aware of the benefits of recreational activities than the other students.